The Effectiviness of Aquatic Therapy as A Rehabilitation Innovation for Stroke Patients: Water as A Medium of Recovery-A Systematic Literature Review - Leticia Freitas Babo; Yurike Septianingrum; Achmad Hidayatullah; Umdatus Soleha; Lono Wijayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke often causes long-term disabilities, significantly affecting motor and functional abilities. Rehabilitation interventions such as aquatic therapy, which utilize the properties of water to enhance movement and reduce pain, have gained increasing attention as innovative rehabilitation strategies. This systematic literature review aims to analyze and summarize the effectiveness of aquatic therapy as a rehabilitation innovation for improving functional recovery in stroke patients. A systematic search was conducted in three databases—PubMed, ScienceDirect, and Google Scholar—for articles published between January 2020 and January 2025. The keywords used in English included “aquatic therapy,” “stroke rehabilitation,” and “water-based therapy.” From the initial search, a total of 45 articles were identified. After screening titles and abstracts based on inclusion criteria (language, publication year, and open-access availability), 20 full-text articles were reviewed in detail. Following critical appraisal and relevance assessment to the research objectives, 10 articles were selected for final analysis. These articles were then synthesized to evaluate the effects of aquatic therapy on functional recovery, particularly focusing on gait and balance improvement in post-stroke patients. This review found 45 studies after identification. Most studies showed that aquatic therapy significantly improved balance, gait, muscle strength, and quality of life among stroke survivors. Additionally, resistance offered by water supports muscle strengthening without overstraining. However, variations in session duration, water temperature, and exercise intensity across studies suggest a need for standardized protocols. Aquatic therapy is an effective and innovative rehabilitation approach for stroke patients, particularly in enhancing motor recovery and quality of life. Future research should focus on standardized intervention protocols and long-term outcomes.